Carbon nanotube-graphene composite film as transparent conductive electrode for GaN-based light-emitting diodes - Kang, C.H. (American Institute of Physics Inc., 2016)
Transparent conductive electrodes (TCE) made of carbon nanotube (CNT) and graphene composite for GaN-based light emitting diodes (LED) are presented. The TCE with 533-Î©/â¡ sheet resistance and 88 transmittance were obtained when chemical-vapor-deposition grown graphene was fused across CNT networks. With an additional 2-nm thin NiOx interlayer between the TCE and top p-GaN layer of the LED, the forward voltage was reduced to 5.12 V at 20-mA injection current. Four-fold improvement in terms of light output power was observed. The improvement can be ascribed to the enhanced lateral current spreading across the hybrid CNT-graphene TCE before injection into the p-GaN layer. Â© 2016 Author(s).